2006
DOI: 10.1007/s00221-006-0391-0
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable effects of the implicit and explicit memory systems on learning control of reaching

Abstract: Adaptive control of reaching depends on internal models that associate states in which the limb experienced a force perturbation with motor commands that can compensate for it. Limb state can be sensed via both vision and proprioception. However, adaptation of reaching in novel dynamics results in generalization in the intrinsic coordinates of the limb, suggesting that the proprioceptive states in which the limb was perturbed dominate representation of limb state. To test this hypothesis, we considered a task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
104
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(114 citation statements)
references
References 27 publications
4
104
0
Order By: Relevance
“…Similarly, Galea et al (2007) recently reported that a concurrent adaptation to two opposing force fields with one arm transferred positively to improve subsequent performance of the same task with other arm across an intrinsic coordinative system, whereas across an extrinsic coordinative system, neither positive nor negative transfer was observed, probably because the information to be transferred was not useful (i.e., incompatible). This interpretation of the current finding also appears to be somewhat consistent with an idea recently proposed by Hwang et al (2006), which states that two internal models are formed during adaptation to novel dynamics, one based on proprioception and the other on vision, and that performance is a sum of these two internal models. Especially given that the planning of reaches to visual and proprioceptive targets may involve distinct sensorimotor transformations , it seems plausible that a conflict between these two types of internal representations may pose a serious computation problem to the motor control system.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Galea et al (2007) recently reported that a concurrent adaptation to two opposing force fields with one arm transferred positively to improve subsequent performance of the same task with other arm across an intrinsic coordinative system, whereas across an extrinsic coordinative system, neither positive nor negative transfer was observed, probably because the information to be transferred was not useful (i.e., incompatible). This interpretation of the current finding also appears to be somewhat consistent with an idea recently proposed by Hwang et al (2006), which states that two internal models are formed during adaptation to novel dynamics, one based on proprioception and the other on vision, and that performance is a sum of these two internal models. Especially given that the planning of reaches to visual and proprioceptive targets may involve distinct sensorimotor transformations , it seems plausible that a conflict between these two types of internal representations may pose a serious computation problem to the motor control system.…”
Section: Discussionsupporting
confidence: 92%
“…It is well known, for example, that if a visuomotor perturbation or a force field is introduced gradually, then subjects successfully adapt to it without ever becoming aware of any perturbation (Jakobson and Goodale, 1989;Kagerer et al, 1997;Klassen et al, 2005;Michel et al, 2007). Even though the effects of an explicit cognitive strategy and implicit, "genuine," motor adaptation are often hard to disentangle, carefully designed experiments allow to separate them (Malfait and Ostry, 2004;Hwang et al, 2006;Mazzoni and Krakauer, 2006). In a similar vein, our present results show that structure learning is part of the implicit motor system.…”
Section: Structure Learning Is Implicit and Automaticsupporting
confidence: 76%
“…Similarly, the current and previous experiments suggest that error clamps can serve as both readouts for processes captured by state-space models and a trigger for additional learning processes. Zero-errorclamp trials, in which feedback is constrained to zero and decoupled from subjects' behavior, have led to insights into learning processes that are well captured by state-space models (Hwang et al, 2006;Criscimagna-Hemminger and Shadmehr, 2008;Tanaka et al, 2009). However, an increasing body of evidence has demonstrated that zero-error clamps are not innocuous but can induce subjects to actively change their learning policy (Pekny et al, 2011;Shmuelof et al, 2011;Vaswani and Shadmehr, 2013).…”
Section: Discussionmentioning
confidence: 99%